The competitiveness of the future organisation from the perspective of internationalisation - Szanyi-Gyenes, Xénia (Vezetéstudomány / Budapest Management Review, 2024)
The Institute of Strategy and Management at Corvinus University of Budapest has launched a large sample survey of Hungarian business leaders in the framework of its own research project. The aim of the research was to get a complex picture of the operating practices of organisations and managers in Hungary and their perceptions of the organisations and managers of the future. The sample of more than 300 people reflects the composition of the Hungarian corporate sector. Taking a complex approach, the research team sought to uncover external environmental influences, internal organisational characteristics, the content of strategic thinking, international growth plans, and inhibitors that may determine the success of the company of the future. The aim of this study is to analyse the competitiveness of domestic firms, focusing on the aspect of internationalisation. Future competitiveness is the basis of a company’s responsiveness, and understanding this is critical in today’s changing environment.